Psychosocial problems and its associated factors among adolescent students in Kirtipur. (2020)
ABSTRACT: Background: Adolescence (10-19 years) is energetic as well as troublesome transitional and critical period from childhood to adulthood of any individual's life. Worldwide, among all the health condition of adolescents (10-19 years) 16% is occupied by mental health. Psychosocial problems include internalizing problem (sad, depression), externalizing problem (conduct disorder, oppositional defiant disorder) and attention problem (ADHD).The objective of this study was to find out the prevalence of psychosocial problems and its associated factors among adolescent students in Kirtipur Municipality. Methodology: A descriptive cross-sectional study was conducted in 292 adolescent students of Grade 8, 9 and 10 by using probability sampling technique in five government and three private schools of Kirtipur Municipality. Data was collected using Self Administered Questionnaire and Pediatric Symptom Checklist- Youth Administered (PSC-Y) tool. Data were analyzed by using SPSS 16 version. Results: The finding revealed that nearly half of the respondents, 46.2% had psychosocial problem among which internalizing problem (38.7%) was the most common followed by externalizing (16.4%) and attention problem (6.2%). The psychosocial problem among adolescents were associated with gender, grade , ethnicity, habit of substance use, using leisure time, trouble with teachers, share problem , family income, family disputes, pocket money, whom they were living with, suicidal thoughts within 3 months and attempted suicide ever with p value < .050. Conclusions: The study concludes that nearly half of the respondents had psychosocial problems. There was significant association between variables as sociodemographic, adolescent characteristics and family factor with psychosocial problems. Those who had trouble with teachers and with family disputes had more psychosocial problems. Hence, exercises need to be done from family to school area to prevent and manage psychosocial problems among adolescent students. Keywords: Adolescent students, Psychosocial problems